Madsarah pada Masa Nidhamiyah - Hasaruddin Hasaruddin (Universitas Islam Negeri Alauddin, 2011)
Human being needs progress in their life to enhance the life quality. For this reasons, they explore some ideas to develop and sustain their culture. In the history of social growth and development, education becomes basic need to accelerate social potency. In Islamic history, Nidham al-Mulk was very care of education. In the early, educational precess was conducted in mosques; however the students day to day become more increased. For this reason, Nidhamul Mulk built some schools as a response on social necessity